The keeper of hidden books : a novel - Martin, Madeline (Hanover Square Press, 2023)
"As bombs rain down on Warsaw and Hitler's forces surround the city, childhood friends Marta and Janina join the war effort using one of the only weapons that still feel safe to them: literature, fighting to preserve their culture and community and finding hope in each other in order to survive.